Transverse maxillary deficiency: treatment alternatives in face of early skeletal maturation - Andrucioli, Marcela Cristina Damião (Dental Press J Orthod, 2020)
Transverse deficiencies should be a priority in orthodontic treatment, and should be corrected as soon as diagnosed, to restore the correct transverse relationship between maxilla and mandible and, consequently, normal maxillary growth. Corrections may be performed at the skeletal level, by opening the midpalatal suture, or by dentoalveolar expansion. The choice of a treatment alternative depends on certain factors, such as age, sex, degree of maxillary hypoplasia and maturation of the midpalatal suture. Thus, the present study discusses different treatment approaches to correct maxillary hypoplasia in patients with advanced skeletal maturation.